2020
DOI: 10.1038/s41598-020-71674-8
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating potential molecular signatures through host-microbe interactions for reactive arthritis and inflammatory bowel disease using combinatorial approach

Abstract: Reactive Arthritis (ReA), a rare seronegative inflammatory arthritis, lacks exquisite classification under rheumatic autoimmunity. ReA is solely established using differential clinical diagnosis of the patient cohorts, where pathogenic triggers linked to enteric and urogenital microorganisms e.g. Salmonella, Shigella, Yersinia, Campylobacter, Chlamydia have been reported. Inflammatory Bowel Disease (IBD), an idiopathic enteric disorder co-evolved and attuned to present gut microbiome dysbiosis, can be correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 84 publications
0
7
0
1
Order By: Relevance
“…Дисбиоз нарушает тонкий баланс между кишечной микробиотой и хозяином, что может привести к заболеванию. Ось «кишечник -микробиота», структурированная на основе взаимодействий «хозяин -микроб», играет важную роль в этиопатогенезе РеА [28]. Результаты нашего исследования подтверждают, что дисбиоз кишечника является отличительной чертой РеА у детей.…”
Section: Discussionunclassified
“…Дисбиоз нарушает тонкий баланс между кишечной микробиотой и хозяином, что может привести к заболеванию. Ось «кишечник -микробиота», структурированная на основе взаимодействий «хозяин -микроб», играет важную роль в этиопатогенезе РеА [28]. Результаты нашего исследования подтверждают, что дисбиоз кишечника является отличительной чертой РеА у детей.…”
Section: Discussionunclassified
“…Multiple levels of interactions between the host and infecting pathogen are emerging as critical to disease induction. Recent in silico studies have indicated, for example, that the Na/H antiporter and kynureninase, among several other proteins, are important targets for such interaction; these and similar kinds of studies will provide critical guidance for researchers to design experimental systems for dissection of those detailed interactions, and for elucidation of pathogenesis mechanisms elicited by novel agents given in previous sections [79].…”
Section: Synovial Pathogenesismentioning
confidence: 98%
“…In these cases, arthritis or other clinical attributes may be associated with some lipo-oligosaccharides from an infecting organism that interact with the patient's innate immune system [20]. It is clear from recent studies that the intestinal microbiome has wide-ranging effects on synovial and other pathogenic processes, and that experimental systems to dissect such long-distance interactions will be critical for the definition of unique pathogenic mechanisms [21][22][23].…”
Section: Key Pointsmentioning
confidence: 99%